Penerapan Metode K-Means Clustering Untuk Menentukan Faktor Resiko Pada Penderita Diabetes Melitus - Melda Septriani; Pareza Alam Jusia; Rudolf Sinaga; Shinta Renova Putri; Firyal Najla 'Afifah (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Diabetes Mellitus is a disease caused by the failure of the pancreas organ in producing the hormone insulin in excess causing increased blood sugar levels and resulting in a lack of insulin. This study discusses the application of the k-means clustering method to determine risk factors for diabetes mellitus. By using the clustering method, data will be grouped into several clusters or groups which in this study compare by applying several data mining tools such as RapidMiner, SPSS, WEKA, and Python. From the results of the comparison carried out resulted in 5 calculations, namely the manual calculation of cluster 1 with a ratio value of 73% being the first priority, calculations using RapidMiner resulting in cluster 3 with a ratio value of 58% being the first priority, calculations using SPSS cluster 2 with a ratio value of 34% being the first priority, and calculations using Python produce cluster 1 with a ratio value of 55% being the first priority.